Perdagangan Elektronik: Suatu Bentuk Pasar Baru yang Menjanjikan? - Losina Purnastuti (Jurnal Ekonomi dan Pendidikan, 2004)
Electronic Commerce is claimed as a form of new market in electronic era. Although most current use of Electronic Commerce occurs at the inter-corporate and inter-organizational levels, Electronic Commerce services aimed at individual consumers are developing rapidly. The internet is a major catalyst in the diffusion of Electronic commerce into an increasing number of economic spheres, and is rapidly harmonizing the general environment in which electronic transactions of all kinds take place. This form of new market is able to create some incentives both in transaction management and business efficiency area. On the other hand, implementation of Electronic Commerce become an issue discussed extensively from many of point of view including: law, economic and technology.